2017
DOI: 10.1136/bmjopen-2017-018494
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of acupuncture for cancer pain: protocol for an umbrella review and meta-analyses of controlled trials

Abstract: Introduction The National Comprehensive Cancer Network guidelines for adult cancer pain indicate that acupuncture and related therapies may be valuable additions to pharmacological interventions for pain management. Of the systematic reviews related to this topic, some concluded that acupuncture was promising for alleviating cancer pain, while others argued that the evidence was insufficient to support its effectiveness.Methods and analysisThis review will consist of three components: (1) synthesis of findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…We found acupuncture effective in reducing CRCI without any report of adverse effects. Acupuncture treatment may also provide other benefits, such as improved mood [ 31 ], reduced pain [ 32 ], and improved quality of life; thus, it warrants further study as part of cancer patient care.…”
Section: Discussionmentioning
confidence: 99%
“…We found acupuncture effective in reducing CRCI without any report of adverse effects. Acupuncture treatment may also provide other benefits, such as improved mood [ 31 ], reduced pain [ 32 ], and improved quality of life; thus, it warrants further study as part of cancer patient care.…”
Section: Discussionmentioning
confidence: 99%
“…In this proposed study, the selection of acupuncture points will be on the basis of comprehensive research including: text mining of premodern Chinese medical literature,60 a systematic review of contemporary clinical trials61 and consultation with clinicians actively involved in providing acupuncture for cancer pain via questionnaires. This protocol will allow the acupuncture procedure to be as consistent with the way acupuncture is typically performed in clinical practice, and aims to provide instruction for future research and clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…[25] In recent years, acupuncture therapy has been widely used in clinical trials of pain caused by prostate cancer, and the recent studies have shown that the therapy could ameliorate the pain caused by prostate cancer to some extent and improve the quality of the life. [26]…”
Section: Discussionmentioning
confidence: 99%